The Role of Information Technology in Human Resource Management: Empirical Evidence from Public Sector of Pakistan - Arbab Gul; Muhammad Ali Ahmad; Hafiz Ahmad; Nuzulul Fatimah; Abid Fareed (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose: At present times, information technology is commonly exploited in different areas of HRM, therefore, most of the public sector organizations have taken initiated to utilize the outstanding services of IT in their HR management functions to optimize and improve their HR departmental efficiency. Information technology has radically changed the way organizations are operated, particularly the HR department. Design/methodology/approach: The current study has been done to identify the key role played by information technology in all human resource departments of public sector organizations operating in Pakistan, and it was found that information technology has changed the operations and functions of the HR department. Findings: The current study has been done to identify the key role played by information technology in all human resource departments of public sector organizations operating in Pakistan, and it was found that information technology has changed the operations and functions of the HR department. Research limitations/implications: The survey questionnaire was adopted; overall 300 questionnaires were distributed, from which 235 returns with a 78% response rate. Practical implications: A simple regression analysis was carried out to check the role of IT in the human resource department of Pakistani public sector organizations, hence found a positive role of IT with r2 = .070.. Paper type: Research paper.